Kajian Nilai Ekonomi dan Lingkungan Akibat Alih Fungsi Lahan Hutan Mangrove menjadi Kawasan Budidaya Rumput Laut - Sri Arfiani Rahim Sila; Andi Ridha Yayank Wijayanti (Jurnal Simki Economic, 2025)
The problem of mangrove forest areas is a very complex issue. Land conversion into fishery ponds, salt ponds, and settlements is a major problem. In recent decades, a new problem has emerged regarding land conversion into seaweed cultivation areas, which also has a major impact on the increasing rate of mangrove forest degradation. This study aims to assess the economic and environmental value of mangrove forest areas that have been converted into seaweed cultivation areas. The study location is in the Pa'baeng-baeng Neighborhood, Bontorannu Village, Jeneponto Regency. The research method is descriptive and quantitative analysis by analyzing descriptive data obtained in the field using an analysis of the calculation of the economic value of mangrove forest areas or the economic valuation of mangrove forests. The results show that the total economic value of mangrove forest areas that have been converted into seaweed cultivation areas is IDR 296,633,850 with a total mangrove forest area of 0.1167 or IDR 21,105,105,906/ha. The total economic value is derived from several benefits derived from mangrove forests, including direct benefits, indirect benefits, option value, and existence value. The conclusion is that a mangrove forest area, if properly managed, will generate significant total economic value. Therefore, if a mangrove forest area converted into a seaweed cultivation area is managed sustainably, the benefits gained by the community from seaweed cultivation will be directly proportional to the benefits offered by the mangrove forest area.